2009
DOI: 10.2105/ajph.2008.139469
|View full text |Cite
|
Sign up to set email alerts
|

Health Disadvantage in US Adults Aged 50 to 74 Years: A Comparison of the Health of Rich and Poor Americans With That of Europeans

Abstract: American adults are less healthy than Europeans at all wealth levels. The poorest Americans experience the greatest disadvantage relative to Europeans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
177
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(195 citation statements)
references
References 41 publications
13
177
1
4
Order By: Relevance
“…26 Those findings were replicated in a representative survey among people age fifteen or older, although prevalences of the conditions in the United States were quite similar to those in Australia and New Zealand. 27 However, a detailed analysis has shown that differences in common risk factors can explain only a small part of the observed differences in the prevalence of chronic diseases between the United States and, for example, England.…”
mentioning
confidence: 83%
“…26 Those findings were replicated in a representative survey among people age fifteen or older, although prevalences of the conditions in the United States were quite similar to those in Australia and New Zealand. 27 However, a detailed analysis has shown that differences in common risk factors can explain only a small part of the observed differences in the prevalence of chronic diseases between the United States and, for example, England.…”
mentioning
confidence: 83%
“…3 In several countries, these later years are accompanied by compromised quality of life, adverse drug events, and disability arising from chronic diseases, such as heart or mental disorders, cancer, stroke, diabetes, and rheumatic disease. 4 Several of these chronic diseases occur in clusters and are associated with health-related behaviours, such as physical inactivity and unhealthy diets. 5,6 This leads to the multimorbidity concept, which has been defined as the coexistence of two or more chronic diseases at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a recent study suggest that older people in continental Europe have better health compared with the USA and the UK (Avendano et al 2009). However, differences between European countries in the health of their older populations have also been widely reported and seem consistent regardless of the health outcome analysed (Eikemo et al 2008;Karlsson et al 2010;Mackenbach et al 2008;Minicuci et al 2004;Olsen and Dahl 2007;Verropoulou 2009).…”
Section: Introductionmentioning
confidence: 99%